The associations of dietary manganese, iron, copper, zinc, selenium and magnesium with cognitive outcomes in Chinese adults: a cross sectional study in Shanghai - Chen, Yujie; Sun, Zhuo; Zhang, Yali; Zhou, Ren; Lin, Xingyu; Du, Yuewen; Xu, Jiayi; Xu, Qi; Zang, Jiajie (Frontiers in Nutrition, 2024)
The role of individual nutrients including vitamins and minerals in cognitive function gained increasing attention in recent years. With regard to the association between dietary minerals and cognitive function, the results of human studies are inconclusive. The objective of this study was to explore the association between mineral intake and cognitive function using the data from Shanghai Health and Nutrition Survey (SHNS) in 2018. In total, 835 adults were included in a cross-sectional study, and completed a three-day dietary record to estimate their average daily intake of minerals. Mini-Mental State Examination(MMSE) was used for the assessment of cognitive function, and logistic regression analyses were performed on participants to examine the association between dietary mineral intake and cognitive performance. The participants were divided into tertiles according to their mineral intake. Participants in the second and third tertile of the dietary copper intake had lower rates of low MMSE scores compared to those in the lowest tertile. We found the adjusted OR and 95%CI values were 0.44 (0.21 -0.89) and 0.40 (0.16 -0.94), respectively. Participants in the second tertile of dietary magnesium intake showed a trend of lower rates of low MMSE score compared to those in the lowest tertile (p=0.06). The adjusted OR and 95%CI values were 0.35 (0.16 -0.72). No significant association were observed between any of the other minerals including iron, zinc, selenium and manganese and cognitive function. Our findings suggest that dietary intake of copper and magnesium may 2 have a protective effect on cognitive performance in elderly over 60 years old. To prevent cognitive decline, elderly should get recommended amounts of copper and magnesium from diet or supplements.